Endocrine-metabolic adaptations in Dorper ewes: comparison between single and twin pregnancies during gestation, parturition, and postpartum - Santarosa, Bianca P. [UNESP] (2022)
The experiment was conducted at Arai & Zumbi farm on sixty healthy Dorper ewes to compare blood glucose, hormonal profile, and insulin resistance evaluation in sheep from conception until 48 h postpartum in single and twin pregnancies. All experimental ewes raised under semi-intensive management system. Sixty animals were selected from 150 estrous synchronized and pregnant ewes. The animals were divided into two groups based on single (G1, n= 30) and twin pregnancies (G2, n= 30). Blood samples were collected at nine time points: immediately after fixed-time artificial insemination (D0); at 30 days (D30), 90 days (D90), 120 days (D120), 130 days (D130), and 140 days (D140) of pregnancy; on the delivery day (DD); and at 24 h (PD1) and 48 h (PD2) postpartum. The results of blood glucose, insulin, glucagon, cortisol, and thyroid hormones (T3 and T4) levels showed significant differences over the analyzed sample times; however, only cortisol showed differences within groups, with the G1 having higher values than the G2 group. The interaction of the groups x nine sample times showed a significant result (P= 0.001) only for glucagon. The number of fetuses directly interfered with the glucagon profile throughout gestation. The glucose, cortisol, glucagon, and the homeostatic model assessment for insulin resistance (HOMA IR) concentrations increased at DD and decreased at PD1 and PD2. T3 and T4 showed different behaviors among the sample times. T3 values presented a decrease from D0 to D90, followed by an increase from D90 to DD. Otherwise, for T4 values, a decrease from D90 to D130 was observed, followed by an increase from D130 to D140. Despite the changes found in the endocrine system and metabolism in Dorper ewes throughout pregnancy, the nutritional management ensured a healthy status during pregnancy, delivery, and postpartum in single and twin gestation, whose HOMA IR profiles remained identical.